Government Type Impact on Tax Policy - Vujčić, Stevan; Vítek, Leoš, 1970-; Pavel, Jan, 1978-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
A series of econometric models is designed to analyze the ideological context of tax policy. The hypotheses tested are that the left-wing governments are associated with higher taxes and more progressive tax mix constructions. A comparison between the older and newer European Union members is outlined. The right-wing and center governments decrease the overall tax-to-GDP ratio in the post-communist, Eastern Bloc countries. The left-wing governments increase the individual income tax revenue in the Western European countries. Social contributions are not subject to ideological frameworks and VAT should be examined using further econometric approaches. A 2016 to 2019 extension has been proposed to the used political parties’ dataset.
Vedoucí práce: Leoš Vítek
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses